The Amount of Working Capital Needed To Develop a Rattan Farming Business - Burhanuddin; Rajindra; Supriadi, Ali; Guasmin; Anggraeni, Rasmi Nur; Kadir, Haris Abd.; Yani, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the amount of working capital needed to develop a rattan farming business. The research was conducted in Sigi District, Central Sulawesi, studying several types of rattan, namely rattan Batang, rattan Lambang, rattan Pahit, rattan Tohiti, and rattan Noko. The sampling process exercised the stratified random sampling method with 50 farmers as respondents. The result shows that the production of rattan Batang farmer exercises the working capital with the amount of Rp. 19.615.954 per hectare every harvesting period, with a net of 19.010.000. The farming of rattan Lambang requires lower working capital of Rp.17.063.318, with a relatively lower net of Rp.13.243.818. Consecutively, rattan Pahit required a working capital of Rp.10.511.318 with the net of Rp.6.691.818, rattan Tohiti requires the working capital of Rp. 13.869.409 with the net of Rp.10.049.909, and rattan Noko required the working capital of Rp.9.294.318 with the net of Rp.5.474.818.